ANALISIS NILAI PERUSAHAAN DARI ASPEK STRUKTUR MODAL, PERTUMBUHAN PENJUALAN, DAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN FARMASI DI BEI PERIODE 2014-2019 - Fauzin Annisa; Agus Dwi Cahya (JURNAL ILMIAH EDUNOMIKA, 2021)
A pharmaceutical company is a healthcare company that focuses on researching, developing, and distributing drugs and/or medical devices. Firm value is the stock market value that reflects the wealth of the owner of a company. The purpose of this research is to examine whether capital structure, sales growth, and dividend policy have an influence on company value in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange for the 2014-2019 period. The research population used is the pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2014-2019 period, totaling 12 companies. The sampling technique used purposive sampling and obtained 6 companies based on the criteria. The analytical method used in this research is multiple linear regression analysis assisted by the SPSS application system. The results showed that simultaneously capital structure, sales growth, and dividend policy have an influence on firm value. Partially the capital structure has a significant negative effect on company value. Sales growth partially has a positive and insignificant effect on company value. Partially the dividend policy has a significant positive effect on company value. Keywords: Capital Structure, Sales Growth, Dividend Policy, and Company Value.